Students’ Motivation in Learning English in Islamic Higher Education - Masruddin, Masruddin; Zuljalal Al Hamdany, Muhammad (Faculty of Education and Teacher Training of IAIN Palopo, 2023)
In the learning process, motivation has an important role because motivation can foster interest in learning. This research will be conducted on semester 1 students of the Islamic Religious Education study program at IAIN Palopo with the aim of describing student motivation in learning English and the factors that influence student motivation in learning English. This research is a descriptive research, which describes existing events by combining quantitative and qualitative. Data collection techniques are questionnaires, observations, and interviews. The subjects of this study were first semester students of the Islamic Religious Education study program who took Basic English courses. The results showed that second semester students of Islamic Religious Education had high motivation in learning English, which consisted of internal and external factors